KONSEP KOMUNIKASI DATA ANTARA PERANGKAT DENGAN WEBSITE MENGGUNAKAN WIRELESS (IoT) - Agus Wibowo; Lawrence Adi Supriyono (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2019)
Abstract The more developed human needs about technology, the more research will be conducted on increasingly rapid technological developments, one example is IoT or Internet of things. It cannot be denied that IoT is a future technology that will be widely used by humans, because IoT has a concept that aims to expand the benefits of internet connectivity that is continuously connected. Allows humans to easily communicate with all equipment connected to the internet network. For this reason, the researcher developed a research on the concept of data communication between devices and interfaces. In this study the website uses wireless which is connected to the internet network. This wireless device will use the ESP8266 wireless module that has been embedded in the Wemos D1 R1 Mini.